2016
DOI: 10.5705/ss.2014.171
|View full text |Cite
|
Sign up to set email alerts
|

Feature screening in ultrahigh dimensional cox's model

Abstract: Survival data with ultrahigh dimensional covariates such as genetic markers have been collected in medical studies and other fields. In this work, we propose a feature screening procedure for the Cox model with ultrahigh dimensional covariates. The proposed procedure is distinguished from the existing sure independence screening (SIS) procedures (Fan, Feng and Wu, 2010, Zhao and Li, 2012) in that the proposed procedure is based on joint likelihood of potential active predictors, and therefore is not a marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…With redundant gene elimination by comparing the Cox filter method with RGE and the original Cox filter method, the resulting signatures have better predictive performance, smaller model sizes and more subtype-specific genes. Furthermore, the present study demonstrated that the use of a pre-filtering process prior to downstream analysis is very beneficial, which is consistent with previous findings by the authors ( 9 ) and the work by others ( 38 , 39 ). Therefore, it is highly recommended to carry out the pre-filtering process, particularly when a very complicated and time-consuming statistical method was selected for downstream analysis.…”
Section: Discussionsupporting
confidence: 93%
“…With redundant gene elimination by comparing the Cox filter method with RGE and the original Cox filter method, the resulting signatures have better predictive performance, smaller model sizes and more subtype-specific genes. Furthermore, the present study demonstrated that the use of a pre-filtering process prior to downstream analysis is very beneficial, which is consistent with previous findings by the authors ( 9 ) and the work by others ( 38 , 39 ). Therefore, it is highly recommended to carry out the pre-filtering process, particularly when a very complicated and time-consuming statistical method was selected for downstream analysis.…”
Section: Discussionsupporting
confidence: 93%
“…With the advent of the biomedical big data era, variable screening for ultrahigh dimensional survival data has been rapidly evolving; see some recent works in [26], [22], [24], and [23].…”
Section: §4 Discussionmentioning
confidence: 99%
“…Remark Although we allow p n to diverge, the asymptotic properties of the BAR estimator in the Section 2.1 are derived for p n < n . In an ultrahigh‐dimensional setting where the number of covariates far exceeds the number of observations ( p n ≫ n ), one may couple a sure screening method with the BAR estimator to obtain a two‐step estimator with desirable selection and estimation properties.…”
Section: Methodsmentioning
confidence: 99%
“…The orders of q n , p n , and n and their relationships depend on the employed screening procedure. For example, coupling the BAR estimator with the sure joint screening procedure has been explored in the work of Kawaguchi…”
Section: Methodsmentioning
confidence: 99%